1988
DOI: 10.1152/ajpheart.1988.255.4.h902
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial activation after unsuccessful defibrillation shocks in dogs

Abstract: To study defibrillation, shocks were given to seven dogs during electrically induced fibrillation, while recordings were made from 56 epicardial electrodes. Shocks were given via electrodes on the left ventricular apex and the right atrium, creating an uneven shock field with much higher potential gradients in the apex than in the base of the ventricles. For unsuccessful 0.01- to 0.05-J shocks, activation occurred soon after the shock at many sites in both the base and the apex. For 0.1- to 0.5-J shocks, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 0 publications
2
46
0
2
Order By: Relevance
“…IW increased as shock strength increased. 4,6,13 3. For both monophasic (MS) and biphasic (BS) shock waveforms, earliest PAs arose, following weak shocks, in areas of high extracellular potential gradient, but moved to areas of low extracellular potential gradient as shock strength increased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IW increased as shock strength increased. 4,6,13 3. For both monophasic (MS) and biphasic (BS) shock waveforms, earliest PAs arose, following weak shocks, in areas of high extracellular potential gradient, but moved to areas of low extracellular potential gradient as shock strength increased.…”
mentioning
confidence: 99%
“…The presence of an isoelectric window (IW) following unsuccessful defibrillation attempts [3][4][5] led to the understanding that an electric shock terminates ongoing fibrillation but then reinitiates it; hence the mechanisms of fibrillation induction and its reinitiation (unsuccessful defibrillation) are the same. Indeed, striking similarities between these mechanisms have been found, particularly with regard to propagation of the first global postshock activation (PA) and IW duration.…”
mentioning
confidence: 99%
“…deexcitation; ultrasound; cardiac mechanics MUCH RESEARCH has concentrated on determining the electrical phenomenon that can predict either the success or failure of ventricular defibrillation. Many studies suggest that excitation (depolarization) of the myocardium plays an important role in defibrillation (2,13,14,16,18) by extinguishing fibrillatory wave fronts [critical mass theory (18)] or by preventing any new fibrillatory wave fronts from forming after the defibrillation shock (2). However, recent studies (4, 11) suggest that deexcitation (repolarization) may be an important factor in determining the success or failure of defibrillation.…”
mentioning
confidence: 99%
“…7,11 With this electrode configuration (RAA3 CS), it has been demonstrated that after a failed shock near the ADFT, the recurrent atrial activation originates from the posterior left atrial wall near the pulmonary veins, 12 a region distant from the defibrillation electrodes, where the shock potential gradient is low. 13 In an effort to reduce the ADFT of the standard RAA3 CS configuration, the benefit of an additional electrode situated across the interatrial septum (SP) was assessed in an earlier study. 14 The delivered-energy ADFT of the configuration with the RAA and CS electrodes in common shocking to the SP electrode (RAAϩCS3 SP) was significantly lower than that of RAA3 CS, and the configuration tested with the lowest mean ADFT was the sequential-shock configuration RAA3 SP/CS3 SP (first shock pathway/second shock pathway).…”
mentioning
confidence: 99%